Short-term treatment with VEGF receptor inhibitors induces retinopathy of prematurity-like abnormal vascular growth in neonatal rats. (February 2016) - Nakano, Ayuki; Nakahara, Tsutomu; Mori, Asami; Ushikubo, Hiroko; Sakamoto, Kenji; Ishii, Kunio
Abstract: Retinal arterial tortuosity and venous dilation are hallmarks of plus disease, which is a severe form of retinopathy of prematurity (ROP). In this study, we examined whether short-term interruption of vascular endothelial growth factor (VEGF) signals leads to the formation of severe ROP-like abnormal retinal blood vessels. Neonatal rats were treated subcutaneously with the VEGF receptor (VEGFR) tyrosine kinase inhibitors, KRN633 (1, 5, or 10 mg/kg) or axitinib (10 mg/kg), on postnatal day (P) 7 and P8. The retinal vasculatures were examined on P9, P14, or P21 in retinal whole-mounts stained with an endothelial cell marker. Prevention of vascular growth and regression of some preformed capillaries were observed on P9 in retinas of rats treated with KRN633. However, on P14 and P21, density of capillaries, tortuosity index of arterioles, and diameter of veins significantly increased in KRN633-treated rats, compared to vehicle (0.5% methylcellulose)-treated animals. Similar observations were made with axitinib-treated rats. Expressions of VEGF and VEGFR-2 were enhanced on P14 in KRN633-treated rat retinas. The second round of KRN633 treatment on P11 and P12 completely blocked abnormal retinal vascular growth on P14, but thereafter induced ROP-like abnormal retinal blood vessels by P21. These results suggest that an interruption of normal retinal vascular development in neonatal rats as a result of short-term VEGFR inhibition causes severe ROP-like abnormal retinal vascular growth in a VEGF-dependent manner. Rats treated postnatally with VEGFR inhibitors could serve as an animal model for studying the mechanisms underlying the development of plus disease. Highlights: Short-term VEGF inhibition interrupts vascular development in neonatal rat retina. An abnormal vascular growth occurs after the interruption of vascular development. The enhanced VEGF–VEGFR pathway contributes to the abnormal vascular growth. Several vascular abnormalities are similar to those of plus disease in ROP.